Harnessing Sorghum Landraces to Breed High-Yielding, Grain Mold-Tolerant Cultivars With High Protein for Drought-Prone Environments - Nagesh Kumar, Mallela Venkata; Ramya, Vittal; Govindaraj, Mahalingam; Sameer Kumar, Chanda Venkata; Maheshwaramma, Setaboyine; Gokenpally, Seshu; Prabhakar, Mathyam; Krishna, Hariprasanna; Sridhar, Mulinti; Venkata Ramana, Maparla; Avil Kumar, Kodari; Jagadeeshwar, Rumandla (Frontiers in Plant Science, 2021)
Intermittent drought and incidence of grain mold disease are two major constraints affecting sorghum production and productivity. The study was aimed at developing drought tolerant sorghum varieties with high protein content and tolerance to grain mold with stable performance using additive main effects and multiplicative interaction (AMMI) and genotype and genotype × environment interaction (GGE) biplot methods. Systematic hybridization between 11 superior landraces followed by subsequent pedigree-based breeding and selection during 2010-2015 evolved 19 promising varieties with white, yellow and brown pericarp grains. These varieties were evaluated for their adaptability and stability for yield in 13 rainfed environments and for grain mold tolerance in three hot-spot environments. Yellow pericarp sorghum variety PYPS 2 (3698 kg/ha; 14.52% protein; 10.70 mg/100g Fe) with tolerance to grain mold was identified as the stable variety using both AMMI and GGE analyses. Four mega-environments were identified for grain yield and fodder yield. Sorghum varieties PYPS 2, PYPS 4, PYPS 8 and PYPS 11 were highly stable in E2 with low grain mold incidence. These varieties are suitable for enhancing sorghum productivity under the present climate change scenario besides meeting nutritional demand of smallholder farmers under dryland conditions.